Psychological functioning of patients with type I diabetes: the relevant role of alexithymia and intolerance to uncertainty - Merlo, Emanuele Maria; Martino, Gabriella; Tutino, Rita; Myles, Liam Alexander MacKenzie; Hill, Sean; Alibrandi, Angela; Lia, Maria Carmela; Minasi, Domenico (Frontiers in Psychiatry, 2025)
IntroductionType 1 Diabetes Mellitus (T1DM) represents a serious condition with high prevalence and increasing incidence. Phenomena such as alexithymia, intolerance to uncertainty and psychopathology are recognized as generally affecting individuals' health status and contributing to the worsening of T1DM. The present study aimed to study the relationships between these variables and differences relative to age and gender of T1DM patients.MethodsA sample of 150 participants aged between 11 and 18 years old with T1DM was recruited. All participants completed the diagnostic protocol, consisting of a sociodemographic questionnaire, Toronto Alexithymia Scale, Intolerance to Uncertainty Scale and Self Administrated Psychiatric Scales for Children and Adolescents (different psychopathological domains). Descriptive, correlational, regression and differential analyses were conducted.ResultsAlexithymia and intolerance to uncertainty predicted psychopathology and significant differences were found among age and gender groups.DiscussionDespite this, more studies are necessary to improve knowledge in the field of psychological functioning in T1DM. Further research to deepen understanding of how alexithymia and intolerance of uncertainty influence psychological functioning in T1DM are indicated.